(untitled) (Bangladesh Journal of Medical Science, 2025)
Objectives This intervention study aimed to evaluate mindfulness meditation as a method of treatment for cancer outpatients for stress reduction and control of symptoms of depression and to find out effects of socio demographic differences. Method Cancer outpatients were randomly selected on separate clinic dates at the National Cancer Institute of Sri Lanka and were enrolled as cases (n=44) and controls (n=30). Volunteers followed training sessions once weekly in addition to home based mindfulness meditation. All participants were asked to complete the “Beck’s Depression” and “Symptoms of Stress” questionnaires prior to intervention and at each session. Controls were assessed based on the identical questionnaire at start and end of 9 weeks. Both groups were heterogeneous in age, sociodemographic characteristics and cancer types / stage. Result At the end of the intervention, patients in the intervention group had significantly lower scores of depressions and stress. Reduction in Beck’s depression score was from 33.21 to 24.56 (p<0.001) in the treatment group, compared to 34.5 to 32.34 (p>0.05) in the control group. Reduction in Symptoms of Stress Inventory from 21.21 to 10.76 (p<0.001) was seen in the intervention group, compared to 22.50 to 25.5 increase in controls. Significant changes (p<0.05) were seen in all age categories, gender, education, income and levels of social interactions. Conclusion Mindfulness meditation programme was effective in decreasing levels of depression and stress in people with cancer, irrespective of socio-demographic backgrounds and cancer types or stages. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 215-221